The relationship between human capital and organisational performance, with the influence of social capital and organisational culture / Lujain Ahmedehsan Mandourah - Mandourah, Lujain Ahmedehsan (Institute of Graduate Studies, UiTM, 2017)
Saudi Arabian economy is in stage of achieving efficiency-driven nation. The kingdom exceeded the stage which depends on the infrastructure to the stage of dependency on the human capital based economy which allow Saudi Arabia to be in the right track of development. Human capital (knowledge, skills and competency), social skills (communication and teamwork) and organizational culture (market, clan, adhocracy and hierarchy) are found to be critical among factors that could be linked and give influence on performance in the organizations. This study therefore aimed to examine the relationship between human capital and organizational performance in Saudi private organizations. It examined also the relationship between human capital and social capital as well as between social capital and organizational performance. Consequently the mediating effect of social capital in the relationship between human capital and organizational performance was also examined. Finally the study examined the moderating effect of organizational culture in the relationship between human capital and organizational performance. The data was analysed based on the random sampling and the self-administered questionnaire, with a response rate of 85%, questionnaire collected from 170 managerial staff that representing the selected organizations in Saudi Arabia. Descriptive statistics, confirmatory factor analysis (CFA), hierarchical multiple regression and Structural Equation Model (SEM) in AMOS were used to analyse the collected data in this study…